A permanent mesoporous organic cage with an exceptionally high surface area - Zhang, Gang; Presly, Oliver; White, Fraser; Oppel, Iris M.; Mastalerz, Michael (Angewandte Chemie. International edition, 2014)
Recently, porous organic cage crystals have become a real alternative to extended framework materials with high specific surface areas in the desolvated state. Although major progress in this area has been made, the resulting porous compounds are restricted to the microporous regime, owing to the relatively small molecular sizes of the cages, or the collapse of larger structures upon desolvation. Herein, we present the synthesis of a shape-persistent cage compound by the reversible formation of 24 boronic ester units of 12 triptycene tetraol molecules and 8 triboronic acid molecules. The cage compound bears a cavity of a minimum inner diameter of 2.6 nm and a maximum inner diameter of 3.1 nm, as determined by single-crystal X-ray analysis. The porous molecular crystals could be activated for gas sorption by removing enclathrated solvent molecules, resulting in a mesoporous material with a very high specific surface area of 3758 m2 g−1 and a pore diameter of 2.3 nm, as measured by nitrogen gas sorption.
Gesehen am 06.10.2020